2013
DOI: 10.1016/j.aat.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the influence of perceived organizational learning capability on user acceptance of information technology among operating room nurse staff

Abstract: Perceived OLC indirectly affects user behavioral intention through the mediation of performance expectancy, effort expectancy, and social influence in the operating room setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
3
16
0
7
Order By: Relevance
“…The significant correlation between social support and intention to use I.T was found also by Ref. [28,34,35]. The variable of behavioral intention toward accepting and integrating I.T was less relevant in this study because the subjects were already (more or less) using the new technology.…”
Section: Discussionsupporting
confidence: 61%
“…The significant correlation between social support and intention to use I.T was found also by Ref. [28,34,35]. The variable of behavioral intention toward accepting and integrating I.T was less relevant in this study because the subjects were already (more or less) using the new technology.…”
Section: Discussionsupporting
confidence: 61%
“…As knowledge and competence become the tools to improve the competitiveness of enterprises, how to strategically establish relationships with partners and improve learning capacity has become an important issue [48][49][50].…”
Section: Olcmentioning
confidence: 99%
“…Despite the supposed improvement in patient outcomes with these patient engagement technology systems, most systems are not reaching their full potential. A major barrier to IT adoption is user acceptance [9]; the technology acceptance model (TAM) states that user acceptance is highly influenced by the perceived usefulness of the system [10]. Moreover, a study conducted that looked at call-light technology found that once nurses were shown a full demonstration of the technology, nurses were more willing to use these systems to improve their workflow and, ultimately, the technology had a positive impact on patient outcomes [11].…”
Section: Introductionmentioning
confidence: 99%